THE RELATIONSHIP OF AUDITEE AND AUDITOR IN PERFORMANCE AUDIT: A LITERATURE REVIEW - Arif, Muhammad Faisal; Syarifuddin, Syarifuddin; Syamsuddin, Syamsuddin; Indrijawati, Aini (AIBPM Publisher, 2024)
This research aims to conduct a literature review of the relationship between auditees and auditors in public sector performance audits based on their roles. Some of the research used in the literature review is research in various countries in Europe and Asia, America, Australia, and New Zealand and is indexed by Scopus through Scimago Journal & Country Rank. Several studies have found that the relationship is not always good. In a cooperative relationship, the auditor requires the auditee's cooperation but at the same time maintains objectivity. Although collaboration can improve audit results, it endangers and hinders auditor independence. Non-cooperative relationships within certain limits make the auditor take strategic actions to influence and control the auditee. This research has limitations because it generally discusses the relationship between auditees and auditors, and does not specifically use research with certain studies such as legitimacy theory or power frameworks, so this research has weaknesses in the focus of studies regarding the relationship between auditees and auditors